PENGARUH KONSENTRASI GELLING AGENT CARBOMER 940 TERHADAP KARAKTERISTIK FISIK ORABASE EMULGEL NISTATIN - Censa Lumayung; Silvy Aldila, Ummi Kalsum, Tunik Saptawati (Jurnal Kesehatan, 2024)
Nystatin is the first line drug for oral candidiasis which is very difficult to dissolve in water. The Orabase Emulgel dosage form has good drug delivery capacity, as gel formulations generally provide faster drug release compared to ointments and creams. Gelling agent components play a role in determining the physical characteristics and permeability of emulgel. The type of gelling agent that will be used is carbomer 940 because it is a strong mucoadhesive. Nystatin is formulated in the form of orabase emulgel with 3 concentrations of carbomer 940, namely F1 (0.5%), F2 (1%), and F3 (2%). The physical characteristics of the preparations observed were organoleptic, homogeneity, pH, emulgel type, viscosity, adhesive power, spreadability, protective power and washability, and stability was tested. The results of the orabase emulgel nystatin preparation on physical characteristics using the MANOVA test (p<0.05) had an effect on pH, viscosity, spreadability and protective power.